EFFECT OF ZINC OXIDE (ZnO) NANO STRUCTURE ORIENTATION ON THE NO GAS SENSOR PERFORMANCE - NIM: 23316001, FITRIANA-
Recently, the rapid development of industrial technology encourages the increase of the air pollution due to the exhaust gases produced by these industrial activities. One of the dangerous exhaust gas that generated from these industrial activities is nitric oxide (NO) because it can endanger the human health and damage the environment even though in low concentrations. Therefore, it is necessary to develop a gas sensor to monitor the presence and the concentration of NO gas. Zinc oxide (ZnO), metal oxide semiconductor, is a materials that widely applied as gas sensors due to its low working temperature, selective, high sensitivity, short response time and recovery time. ZnO tend to grow with (002) orientation or random orientation so this study analyzed the influence of these orientations on its performance as NO gas sensor. In this study, ZnO nanorods film with (002) orientation and random orientation were successfully synthesized on glass substrate using two methods. The first was dip coating method for seed layer formation and the second was chemical bath deposition (CBD) method for the growth of ZnO nanorods. The ZnO nanorods films with (002) orientation was formed by the seed layer precursor solution using diethanolamine (DEA) while the ZnO nanorods film with random orientation was synthesized by seed layer precursor solution without DEA. The CBD process for the growth of both ZnO nanorods films was applied at 60C for 20 hours. The XRD results showed that the ZnO films with seed layer synthesized using DEA only had one dominant peak that correspond to the (002) plane of ZnO, while the ZnO film with seed layer synthesized without DEA had three dominant peaks which correspond to the ( 100), (002), and (110) plane of ZnO. Based on the SEM result, it was known that the ZnO on both films were nanorods with a hexagonal structure. The nanorods in the ZnO film with (002) orientation were 83 nm and 666 nm in diameter and length respectively, while the nanorods in the ZnO film with a random orientation had a diameter of 82 nm and a length of 679 nm. The SEM results also confirmed that the nanorods in ZnO film with (002) orientation were growth perpendicular to the substrate while nanorods in the ZnO film with random orientation were growth to several directions. HRTEM results showed that the SAED pattern of the sample confirmed that the ZnO film with seed layer synthesized using DEA growth in (002) orientation while the ZnO film with seed layer synthesized without DEA growth in random orientation. The response of ZnO films at a temperature range of 160C-350C under 30 ppm NO gas indicate that the optimum working temperature of (002) oriented ZnO film was 200C with response of 57.28% while the optimum working temperature of randomly oriented ZnO film was 300Ã‚Â° C with response of 47.5%. At this optimum working temperature, the ZnO films were also tested under 30 ppm CO gas and the results showed that the response was 37.33% and 29.31 % for the (002) oriented ZnO nanorods film and randomly oriented ZnO nanorods film, respectively. It was indicated that both ZnO films were more selective in detecting NO gas than CO gas. In this study, the ZnO films were tested at various NO gas concentrations, which were 10 ppm, 30 ppm, 50 ppm, 70 ppm, and 90 ppm under temperature 200C. The response of the ZnO nanorods films were increased with increasing NO gas concentration. Furthermore, it was also known that the (002) oriented ZnO films had higher response and sensitivity than randomly oriented ZnO film. The analysis results of the response time and recovery time showed that (002)-oriented ZnO film had faster response time and recovery time than randomly-oriented ZnO film. Based on the results, it can be conluded that the (002) oriented ZnO had better performance for NO gas sensor due to its lower optimum working temperature, higher response and sensitivity than randomly oriented ZnO film.